Metabolic profile in patients with prostate cancer - E. V. Pomeshkin; A. V. Smirnov; S. V. Popov; I. N. Orlov; A. I. Bragin-Maltsev (Исследования и практика в медицине, 2023)
Purpose of the study. To evaluate the levels of metabolic markers in patients with prostate cancer (PCa) in comparison with patients with benign prostatic hyperplasia (BPH).Patients and methods. 108 patients were included in the study. The majority of patients had comorbidities: coronary heart disease, hypertension, and almost one third of patients had type 2 diabetes mellitus. Median (Me) age was 67 (64–74), body mass index was 25.9–34.7. The main study group included 54 patients with histologically verified prostate cancer, the comparison group consisted of 54 patients with benign prostatic hyperplasia (BPH). The level of basic biochemical parameters, glomerular filtration rate, lipidogram, total prostate-specific antigen (PSA), total testosterone was determined in all patients.Results. When comparing anamnestic and biochemical parameters, the groups were not statistically significantly different. When comparing the groups by lipid status, it turned out that in the group with RPW, in contrast to the group of patients with BHP, statistically significantly higher levels of total cholesterol (5.13 (3.3–10,4) and 4.60 (2.5–6.3)) mmol/L, respectively, p = 0.023), low–density lipoproteins (2.93 (0.8–5.9) and 2.60 (0.9–4.2) mmol/L, respectively, p = 0.035), triglycerides (2.10 (1.0–8.0) and 1.70 (0.5–7.3) mmol/L, respectively, p = 0.048). In case of dyslipidemia, an increased risk of developing PCa was identified. Correlation analysis revealed a direct moderate relationship between total PSA levels and total cholesterol concentration (r = 0.51).Conclusion. Our study revealed that in the PCa group, there was a higher level of total cholesterol, low-density lipoproteins, and triglycerides, in contrast to the group of patients with BPH. Additionally, in the group of patients with BPH, dyslipidemia was a risk factor in the development of PCa, which should be taken into account in PCa prevention and diagnosis.